2012
DOI: 10.2308/ajpt-50308
|View full text |Cite
|
Sign up to set email alerts
|

Audit Partner Tenure and Cost of Equity Capital

Abstract: SUMMARY We examine whether audit engagement partner tenure and rotation affect investors' perceptions, as proxied by the ex ante cost of equity capital. We find that partner tenure has a nonlinear relation with the ex ante cost of equity capital for non-Big 4 audit engagements prior to the introduction of partner rotation requirements, and that the imputed gains from partner tenure appear similar to the imputed gains of having a Big 4 auditor. Consistent with the tenure results, we also find tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
47
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 46 publications
9
47
0
Order By: Relevance
“…Azizkhani, Monroe and Shailer () use a sample of Australian firms to investigate the association between the cost of equity capital and both audit firm and audit partner tenure. With respect to audit firm tenure, the authors find a nonlinear association between auditor tenure and the cost of equity capital for non‐Big 4 auditors, whereby perceptions of audit quality initially improve over tenure and then begin to deteriorate after approximately 10.7 years (Azizkhani et al ., ). The authors find no association between audit firm tenure and the cost of equity capital for Big 4 auditors.…”
Section: Background and Prior Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Azizkhani, Monroe and Shailer () use a sample of Australian firms to investigate the association between the cost of equity capital and both audit firm and audit partner tenure. With respect to audit firm tenure, the authors find a nonlinear association between auditor tenure and the cost of equity capital for non‐Big 4 auditors, whereby perceptions of audit quality initially improve over tenure and then begin to deteriorate after approximately 10.7 years (Azizkhani et al ., ). The authors find no association between audit firm tenure and the cost of equity capital for Big 4 auditors.…”
Section: Background and Prior Literaturementioning
confidence: 99%
“…First, Azizkhani et al . () utilize Australian data and examine a relatively small sample of observations during a time period that was primarily before the accounting scandals in the early 2000s. We utilize a much larger sample of observations from the United States and our sample period extends from 2003 to 2010.…”
Section: Background and Prior Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Azizkhani et al () found a U‐shaped relationship between audit partner tenure and the cost of equity capital. They showed that the cost of equity capital decreases up to a threshold year, and then increases as the audit partner tenure increases.…”
mentioning
confidence: 99%
“…3 Studies use the EP identification to document that individual engagement partners' tenure and rotation are related to perceived audit quality (e.g., Azizkhani, Monroe, and Shailer 2013;Lennox, Wu, and Zhang 2014). The researchers suggest that mandatory rotation of engagement partner leads to higher quality audits in the years immediately surrounding rotation.…”
Section: Introductionmentioning
confidence: 99%